Design of Active Prosthetic Knee Adapted with Uneven Terrain - بركات نيرودا; داؤد نائل; صعيدي الاء (Latakia University Journal -Engineering Sciences Series, 2022)
The currently available commercial knees simulate the human knee by performing one rotational movement (extension / flexion), research studies in this field focus also on the same issue, this research aims to design a prosthetic knee that can perform two rotational movements, in addition to getting as close as possible to the kinematic and kinetic characteristics of the intact human knee. The joint in this paper is a U-Joint type that provides two rotational movements., the first (extension/flexion) is controlled by a Series Elastic Actuator SEA, and the second (abduction / adduction) is controlled by a mechanism called gas spring. The design considers the height and weight of an average Syrian male subject. A structure analysis was performed using the finite element method to ensure its ability to do the required job when exposed to different possible loads.